2001
DOI: 10.1021/es002046y
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Remote Sensing of Vehicle Exhaust by Dispersive Absorption Spectroscopy. 2. Direct On-Road Ammonia Measurements

Abstract: Remote sensing was employed for the first time to measure NH3 levels in the exhaust of on-road light duty motor vehicles. The sensor also measured the concentration of CO2, CO, hydrocarbons, and NO, among other pollutants, in the emitted exhaust. Field measurements were conducted at a Los Angeles freeway on-ramp; vehicles traveled at cruise speeds between 20 and 25 m s(-1) (45-55 mi h(-1)). Mean fleet NH3 levels of 44.7 +/- 4.1 ppm were observed. These emissions exhibited a highly skewed distribution: 50.1% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 83 publications
(110 reference statements)
2
31
1
1
Order By: Relevance
“…In 1983, Pierson et al [4] reported 1.3 mg of NH 3 /km. In 1988, Fraser et al [5] stated that the ammonia emission was 60 mg/km, and in 2001, Baum et al [6] reported that it reached 94 mg/ km. As a result of that large rate of increase, the NH 3 factor published by US-EPA [7] to help predict emissions by gasoline cars was exceeded already in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, Pierson et al [4] reported 1.3 mg of NH 3 /km. In 1988, Fraser et al [5] stated that the ammonia emission was 60 mg/km, and in 2001, Baum et al [6] reported that it reached 94 mg/ km. As a result of that large rate of increase, the NH 3 factor published by US-EPA [7] to help predict emissions by gasoline cars was exceeded already in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…O sistema de medida respondeu proporcionalmente para a concentração de amônia na fase gasosa e tempo de pré-concentração. Amônia foi também determinada na exaustão de motores de veículos através de um sensor eletroquímico 114 , que também mediu as concentrações de CO 2 , CO, hidrocarbonetos, NO e outros poluentes emitidos na exaustão. O polímero polianilina foi sintetizado e dopado com ácido acrílico, para ser usado como um sensor de amônia gasosa numa ampla faixa de concentrações (1-600 ppm) 115 .…”
Section: Métodos Para Determinação Da Amônia Atmosféricaunclassified
“…[9,10,11] The measurement apparatus is calibrated and evaluated by connecting the sample cell to a gas manifold system. Synthetic mixtures (carbon dioxide, CO 2 , carbon monoxide, CO, and ammonia, NH 3 ) of known concentration are prepared by blending certified gases using mass flow controllers.…”
Section: Signal Processingmentioning
confidence: 99%